How to not miss alveolar echinococcosis in hepatic lesions suspicious for cholangiocellular carcinoma - Müller, Jan; Stojković, Marija; Berger, Anne Katrin; Rosenberger, Kerstin; Schlett, Christopher L.; Kauczor, Hans-Ulrich; Junghanss, Thomas; Weber, Tim (Abdominal radiology, 2016)
Hepatic alveolar echinococcosis (AE) resembles intrahepatic cholangiocarcinoma (ICC) on radiological imaging. The purpose of this study was to identify criteria to discriminate AE from ICC with CT and MR Imaging.